The problematics of financialization – On the important (but neglected) horizontal axis of organizational action. (December 2022) - Graaf, Johan; Kraus, Kalle; Strömsten, Torkel
Abstract: This study traces the financialization of the Swedish telecommunications company Ericsson from 1990 to 2000. Previous research has explained financialization in terms of the influence of actors (e.g., fund managers and financial analysts) and accounting technologies (e.g., increased use of stock options and financially oriented incentive systems) associated with what Hopwood (1983) labelled the vertical axis of organizational action. Our case, however, shows that the horizontal axis of organizational action (Ericsson's inter-firm relationship with the lead firm Vodafone) played a pivotal role. This horizontal axis is theorized by drawing on accounting literature relating to inter-firm relations and more general literature concerning two types of supplier adaptations in global value chains: first, the design and exchange of products; and second, production processes and organizational structure. Horizontal pressure from Vodafone compelled Ericsson to adapt its product design and development processes, which in turn created conditions for vertical pressures to accrete. We found that actors (an Ericsson supply chain manager and Vodafone's purchasing director) and accounting technologies (a global price list) informing the horizontal axis of organizational action played vital roles in supplier adaptations. Such actors and accounting technologies are viewed as 'purely operational' in prior work, but our findings suggest they initiated and sustained a financialization process with far-reaching and long-lasting effects within Ericsson. Indeed, both actors and accounting technologies which, at first glance, may seem to have little connection to financialization processes, played a central role through the constitution of a horizontal axis of organizational action.